A class of rigid linker-bearing glucosides for membrane protein structural study - Sadaf,A; Mortensen,JS; Capaldi,S; Tikhonova,E; Hariharan,P; Ribeiro,O; Loland,CJ; Guan,L; Byrne,B; Chae,PS (Chemical Science, 2015)
Membrane proteins are amphipathic bio-macromolecules incompatible with the polar environments ofaqueous media. Conventional detergents encapsulate the hydrophobic surfaces of membrane proteinsallowing them to exist in aqueous solution. Membrane proteins stabilized by detergent micelles are usedfor structural and functional analysis. Despite the availability of a large number of detergents, only a fewagents are sufficiently effective at maintaining the integrity of membrane proteins to allow successfulcrystallization. In the present study, we describe a novel class of synthetic amphiphiles with a branchedtail group and a triglucoside head group. These head and tail groups were connected via an amide orether linkage by using a tris(hydroxylmethyl)aminomethane (TRIS) or neopentyl glycol (NPG) linker toproduce TRIS-derived triglucosides (TDTs) and NPG-derived triglucosides (NDTs), respectively. Membersof this class conferred enhanced stability on target membrane proteins compared to conventionaldetergents. Because of straightforward synthesis of the novel agents and their favourable effects ona range of membrane proteins, these agents should be of wide applicability to membrane protein science.